(untitled) (Research, Society and Development, 2021)
Objective: to explain the growing number of people suffering from psychosomatic disorders in a pandemic period, as well as the difficulty in obtaining psychological care. Methodology: this is a literature review from the chosen articles, the results of which were analyzed and discussed, and a review of the content addressed was presented. According to the following inclusion criteria: in Portuguese, with psychosomatic diseases as the main subject; 07 articles were selected from the Google Scholar and SciELO database. Of these 07 bibliographies were related to the theme and followed for a thorough reading and further analysis. Results: in view of the data collected, it was noticed that during the pandemic of the new corona virus there was an increase in psychosomatic illnesses and in levels of anxiety, depression, sleep difficulties and stress, with women and professionals in the area being the main groups affected. health, in addition, difficulties in psychological care were present in all sectors. Conclusion: the study analyzed that the pandemic brought a lot of damage to the mental and physical health of individuals, having as factors the dissemination of negative or false news, in addition to the loss of loved ones, and difficulties in psychological care, such as the reduction of services provided in CAPS, which generated more mental suffering in almost half of the population.